Composition Changes in the Boreal Mixedwood Forest of Western Quebec Since Euro-Canadian Settlement - Marchais, Mathilde; Arseneault, Dominique; Bergeron, Yves (Frontiers in Ecology and Evolution, 2020)
Colonisation of eastern North America has generated significant modifications in forest composition. In regions highly influenced by human activity, historical ecology can be used to reconstruct pre-settlement forest composition. In this study, we reconstruct the composition of the pre-settlement (1909-1937) forest of a 4,134 km2 sector of the boreal mixedwood forest using early land survey archives. The pre-settlement composition was compared with modern composition using recent eco-forest inventories (1980-2008), and the influence of surficial deposits types on the spatial structuration of compositional changes was assessed. During the pre-settlement period, the landscape was primarily dominated by spruce, which was evenly distributed across surficial deposit types. Trembling aspen, although frequent, rarely dominated stands. In contrast, the present-day landscape is dominated by trembling aspen, notably on clay and till deposits. In general, conifers have undergone a severe reduction in frequency. Spruce and pine forests are today mainly restricted to organic and sandy surficial deposits compared to their distribution during the pre-settlement period. Composition changes observed in western Abitibi are essentially the results of fires and forest harvesting, but surficial deposits have contributed in structuring the current abundance and spatial distribution of the different taxa. In the context of sustainable forest management, considerable effort should be deployed to restore conifer dominance in the region, notably on the fertile deposits that appear particularly susceptible to composition changes.